An introduction to electrical science - Waygood, Adrian (2013)
"Written in an informal conversational style, with some interesting reflections on the historical background to the subject matter, the author uses a combination of easy-to-understand explanations together with a unique step-by-step approach to developing many of the topics. The content ranges from the electron theory of electricity up to an introduction to three-phase alternating-current systems. In an unorthodox approach to alternating current theory, the author encourages readers not to attempt to memorise any of the numerous equations but, instead, to treat the subject as a practical exercise in simple geometry and trigonometry which anyone can master"--
Includes index.
Keywords: Electrical engineering -- Textbooks; Electrical engineering -- Equipment and supplies -- Textbooks; Electricity -- Textbooks; TECHNOLOGY & ENGINEERING / Electrical; TECHNOLOGY & ENGINEERING / Engineering (General).